Essential readings in management learning - Grey, Christopher, 1964-; Antonacopoulou, Elena P. (Sage, 2004)
This volume brings together some of the best writing published in the journal Management Learning since its re-launch under this title in 1994. This collection provides readings grouped under six key headings which reflect where some of the most influential and provocative work in the field has been done over recent years, namely: Organizational Learning and Learning Organizations; Individual Learning; Learning and New Technology; Critical Approaches to Management Education; Pedagogical Practice; Globalization and Management Learning; Along with an editorial introduction, this volume will prov.